Substituted imidazopyridazines are potent and selective inhibitors of Plasmodium falciparum calcium-dependent protein kinase 1 (PfCDPK1) - Chapman, Timothy M. (Elsevier Science Ltd, 2013)
A series of imidazopyridazines which are potent inhibitors of Plasmodium falciparum calcium-dependent protein kinase 1 (PfCDPK1) was identified from a high-throughput screen against the isolated enzyme. Subsequent exploration of the SAR and optimisation has yielded leading members which show promising in vitro anti-parasite activity along with good in vitro ADME and selectivity against human kinases. Initial in vivo testing has revealed good oral bioavailability in a mouse PK study and modest in vivo efficacy in a Plasmodium berghei mouse model of malaria.